Characterization of Active Carbon Pineapple Skin (Ananas comosus) as Absorbent of Heavy Metal Copper (Cu) with NaOH and NH4OH Activators - Herdie Idriawien Gusti; Syahdam Karneng; Miftahul Jannah Abd Haris; Musdalifah1 (Hayyan Journal, 2025)
This research aims to evaluate the potential of pineapple peel as a raw material for making activated carbon, as well as comparing the effectiveness of NaOH and NH4OH activators in the activation process. Activated carbon is produced through a carbonization and chemical activation process, then its quality is tested based on the Indonesian National Standard (SNI) 06-3730-1995. The research results show that activated carbon from pineapple peel meets SNI standards in terms of ash content and water content, with each not exceeding the maximum limits of 10% and 15%. The yield of activated carbon activated with NH4OH (87.5%) was higher than NaOH (79.4%). In addition, the water content of activated carbon with NH4OH (1.07%) is lower than NaOH (1.42%). Although the iodine absorption capacity of activated carbon from pineapple peel is still below the minimum SNI standard (750 mg/g), NH4OH shows better results in adsorption of the heavy metal Cu (0.0041 mg/g) than NaOH (0.0015 mg/g ). The FTIR spectrum shows the presence of diverse functional groups, indicating complex chemical interactions. Based on the results of this research, pineapple peel has good potential as a raw material for activated carbon, with NH4OH as a more effective activator in improving the quality and adsorption ability of activated carbon.